2016
DOI: 10.1371/journal.pgen.1006258
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of 18 Ancestral and Horizontally-Acquired Regulatory Proteins upon the Transcriptome and sRNA Landscape of Salmonella enterica serovar Typhimurium

Abstract: We know a great deal about the genes used by the model pathogen Salmonella enterica serovar Typhimurium to cause disease, but less about global gene regulation. New tools for studying transcripts at the single nucleotide level now offer an unparalleled opportunity to understand the bacterial transcriptome, and expression of the small RNAs (sRNA) and coding genes responsible for the establishment of infection. Here, we define the transcriptomes of 18 mutants lacking virulence-related global regulatory systems t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
140
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(153 citation statements)
references
References 119 publications
11
140
0
Order By: Relevance
“…Anaerobic activation of fnrS is mainly dependent on Fnr, but is also affected by ArcA and CRP (Durand and Storz, ). It has been reported that Fur, the ferric uptake regulator, also affects fnrS expression (Colgan et al , ). Fur is known to positively regulate HilD expression.…”
Section: Resultsmentioning
confidence: 99%
“…Anaerobic activation of fnrS is mainly dependent on Fnr, but is also affected by ArcA and CRP (Durand and Storz, ). It has been reported that Fur, the ferric uptake regulator, also affects fnrS expression (Colgan et al , ). Fur is known to positively regulate HilD expression.…”
Section: Resultsmentioning
confidence: 99%
“…Their genes (Argaman et al, 2001;Wassarman et al, 2001;Vogel et al, 2003) are transcriptionally activated by the OmpR-EnvZ two-component system, e.g., under high osmolarity conditions (Guillier & Gottesman, 2006;Brosse et al, 2016). OmrA, but not OmrB, is additionally under the control of the stress sigma factor r s (rpoS; Lévi-Meyrueis et al, 2014;Peano et al, 2015;Colgan et al, 2016). Both sRNAs associate with Hfq in vitro (Holmqvist et al, 2010) and in vivo (Wassarman et al, 2001;Zhang et al, 2003;Chao et al, 2012;Tree et al, 2014;Holmqvist et al, 2016); the sRNAs are destabilized in Δhfq cells (Holmqvist et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…HilC and RtsA are AraC-like transcriptional regulators that bind the same DNA sequence recognized by HilD; HilC is encoded within SPI-1, whereas RtsA is encoded in another island. HilD also controls the expression of many other virulence genes located outside SPI-1, including acquired and ancestral genes, directly, or indirectly through HilA, InvF or other regulators (12,(17)(18)(19)(20)(21)(22)(23)(24)(25). In agreement with its role as a master transcriptional regulator for a high number of genes, the expression, concentration and activity of HilD is tightly controlled.…”
Section: Introductionmentioning
confidence: 99%